Herrada Bazán, Víctor. La exclusión de socios en la Ley General de Sociedades. Lima: Gaceta Jurídica, 2017 - Cabrera Céspedes, Armando Miguel (Universidad ESAN, 2019)
In the 21st century, the growth of various industries and economic sectors has generated that the companies try to adapt to the demands of the of the market. Within the legal scope, such adaptation is not alien, as it establishes a direct relationship with the corporate form adopted by the companies in reality, being that a certain company will be constituted (anonymous, limited, closed, etc.) according to the functionality and treatment legal basis for its creation. With this, a diversity arises of problems and issues that deserve special attention. Within the contemplated by the General Companies Law (hereinafter, LGS), it is presented the corporate figure of the exclusion of partners, a subject that has not been studied in depth in our national legislation.

En pleno siglo XXI, el crecimiento de las diversas industrias y sectores económicos del país ha generado que las empresas procuren adaptarse a las demandas del mercado. Dentro del ámbito legal, dicha adecuación no es ajena, pues se establece una relación directa con la forma societaria adoptada por las empresas en la realidad, siendo que se constituirá determinada sociedad (anónima, en comandita, cerrada, etc.) de acuerdo con la funcionalidad y tratamiento legal que fundamenta su creación. Con ello surge una diversidad de problemas y cuestiones que merecen especial atención. Dentro de lo contemplado por la Ley General de Sociedades (en adelante, LGS), se presenta la figura societaria de la exclusión de socios, tema que no ha sido estudiado a profundidad en nuestra legislación nacional.
Keywords: General Law on Companies; Ley General de Sociedades; Exclusion of partners; Exclusión de socios; https://purl.org/pe-repo/ocde/ford#5.05.01